Verfassungsaufsicht in der Europäischen Union Eine akteurszentrierte Analyse der Rechtsstaatlichkeitskrise der Europäischen Union - Schmidt, Matthias (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, 2022)
This book offers, in five parts, an analysis of the so-called rule of law crisis in the EU. The first part focuses on the concepts that help to understand the rule of law crisis, in particular that of "systemic deficiencies in the rule of law". In order to shine light on the complex concept of "rule of law" included in Art. 2 TEU, the author focusses on the operationalisation of the rule of law in recent CJEU jurisprudence. The second part of the book is devoted to developments in certain Member States that make up the rule of law crisis. Special attention is paid to Poland and Hungary. The third part deals with the main thesis of the book: why it is useful to conceive of the measures taken in response to the rule of law crisis as "constitutional supervision" in EU law. The merits and roots of this concept are discussed in detail. On this basis, the fourth part presents the core of the analysis: the different mechanisms of EU constitutional supervision. After introducing its different actors, the work focuses on the activities of the European Commission. The final part concludes with an outlook.